Direito fundamental à educação e as famílias homoafetivas: uma reflexão sobre o currículo multicultural nas escolas - Pessanha, Jackelline Fraga (2011)
The present study examines the means of structuring multicultural curricula grounded on sexual diversity, to protect the fundamental right to equality, the respect for differences, the freedom of sexual orientation and education, targeting the question: Given the increasing presence of children of homosexual parents, how to design a multicultural curriculum which involves diversity and ensues simultaneously the realization of the fundamental right to equality and the recognition of difference among students? Since children of homosexual families are a growing number, the school must be a democratic environment, with education free of prejudice and differentiation, in order to allow for a dialogue among all students. When enforcing the proposal to build effective means and / or forms of a structured curriculum, the school program must not disregard children from same-sex families, especially in view of the fact that curriculum is the chief element in a political-pedagogical project. Multicultural curricula must promote equality and eliminate discrimination, whether it be individual or institutionalized, and support structured educational activities, as such practices are most important for educational inclusion of all students. The relevance of this theme arises from the search for fundamental rights embedded in the Constitution, which guarantees to all citizens the right to equality, respect for differences, freedom of sexual orientation, and especially, the right to education, being of great social and legal value. The method used in this inquiry is dialectical, for it analyzes the phenomena by means of reciprocal actions, rooted in the contradiction, and in the dialectical changes occurring in society, which affect the entire context of the multicultural curriculum. This paper is divided into three chapters, which focus on fundamental rights of homosexual families, education and diversity, and multicultural curricula. In the effort of designing a multicultural school, education system must be widely open to all minorities of society, be blacks, Indians, women, and homosexual or single-parent or socio-affectionate parent families. It is necessary to appreciate social and ethnic diversity, with different lifestyles, cultures, identities and social experiences to assure educational opportunities, considering that legislation has extended the elements to be covered by the curriculum, in order for it to be broader and accepted by all students and educators.